Using Brain Computer Interaction in Programming Problem Solving - Eloy, Joana (2019)
the use of Brain-Computer Interaction (BCI) technology to better understand and promote learning processes. In this context, the idea is to obtain information about the user and deduce his/her mental states (e.g. workload, attention, concentration) through user’s electroencephalogram signals (EEG). In future researches, we are interested in understanding the performance of users in tasks involving high cognitive processes such as programming problem solving. The goal would be to find metrics and strategies that are adaptable to each user, looking to increase the success in programming learning. However, this work represents a set of initial works that provides an overview of how brain computer interaction can intersect with issues in the field of education, namely in design and in cognitive attention and concentration processes. The main goal of this study is to analyse several cognitive parameters (Attention, Concentration) of crucial importance for learning, while students do a programming problem solving oriented task activity. For a better characterization of the data, an analysis of the ERD/ERS complex was performed, thus analysing the event synchronization or desynchronization, in order to reflect the activation or inhibition of the cerebral activity during the game and consequently the absorption of information and the capacity of learning. Additionally, five EEG features were extracted, namely the powers of Delta, Theta, Alpha, Beta and Gamma bands, as well as, the variability of these bands’ energy.